La Iglesia Católica colombiana en los años 60 según los documentos del Archivo del Concilio Vaticano II - Michele Merenda (Nuevo mundo - Mundos Nuevos, 2025)
During the 1960s, the Colombian Catholic Church exhibited, on the one hand, a greater social sensitivity to the problems affecting the population and, on the other, a series of difficulties, both internal and external, which gradually reduced its power and influence. The aim of this paper is to analyze this situation using documents from the Second Vatican Council, preserved in the Vatican Apostolic Archives. These documents, so far little explored by Colombian historiography, allow us to consider the perspective of the protagonists, the prelates, placing the study of the Colombian Church in a transatlantic and transnational perspective. Due to limitations in access to the documentation, the work focuses on the period between 1959 and 1965, although it includes observations related to the entire decade.